2018
DOI: 10.48550/arxiv.1803.06325
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Lie algebras and $v_n$-periodic spaces

Abstract: We consider a homotopy theory obtained from that of pointed spaces by inverting the maps inducing isomorphisms in vn-periodic homotopy groups. The case n = 0 corresponds to rational homotopy theory. In analogy with Quillen's results in the rational case, we prove that this vn-periodic homotopy theory is equivalent to the homotopy theory of Lie algebras in T (n)-local spectra. We also compare it to the homotopy theory of commutative coalgebras in T (n)-local spectra, where it turns out there is only an equivale… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
19
0

Year Published

2018
2018
2020
2020

Publication Types

Select...
3
2

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(19 citation statements)
references
References 37 publications
(109 reference statements)
0
19
0
Order By: Relevance
“…Our methods in fact provide a useful tool in the study of v h -periodic spaces through spectral Lie algebras. For example, Theorem 2.5 was originally used in [10] to establish a more direct relation between the Bousfield-Kuhn functor and spectral Lie algebras which does not suffer from the aforementioned convergence issues.…”
Section: Introduction and Main Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…Our methods in fact provide a useful tool in the study of v h -periodic spaces through spectral Lie algebras. For example, Theorem 2.5 was originally used in [10] to establish a more direct relation between the Bousfield-Kuhn functor and spectral Lie algebras which does not suffer from the aforementioned convergence issues.…”
Section: Introduction and Main Resultsmentioning
confidence: 99%
“…Remark 5.5. In Theorem 2.11 of [10] it is in fact shown that Φ v (M ℓ ) is simply the direct sum of all its homogeneous layers (and similarly for higher heights h and appropriate type h complexes in place of M ℓ ); by the arguments above this can indeed not be equivalent to the infinite product. However, the arguments of [10] require more technology than is necessary to include here.…”
Section: Divergence On Moore Spacesmentioning
confidence: 99%
See 2 more Smart Citations
“…It was also recently used in [Heu18] to generalize Quillen's rational homotopy theory to higher chromatic heights. We shall now describe an application of Theorem A, i.e.…”
mentioning
confidence: 99%